Measuring Gender Differences in Information Sharing Using Network Analysis: the Case of the Austrian Interlocking Directorship Network in 2009 - Carlo Drago; Livia Amidani Aliberti; Davide Carbonai (Fondazione Eni Enrico Mattei (FEEM), 2014)
In recent literature a relevant problem has been the relationship between career/personal contactnetworks and different career paths. In addition the recent advances in social capital theory have shown the way in which networks impact on personal careers. In particular womens careers appear to be negatively affected by the informational network structure. The main contribution of this work is to propose empirical evidence of this phenomenon by considering the gendered directorship network with relation to Austria and to show the structural differences by gender in the network. By using community detection techniques we have found various communities in which females seem not to be present at all, where females show significantly fewer contacts than males in the network, and finally where the proportion of males exceeds 91%. The results show the predominant role in the network of male directors;these differences are very relevant if we consider the network as a tool of vehicle information and as a power mechanism. In this paper we wish to make an original contribution to the debate of the well-known glass-ceiling effect.
Keywords: M14; M5; C60; C4; 330; Glass ceiling; Gender Diversity; Social Network Analysis